2015
DOI: 10.1017/s1755773915000338
|View full text |Cite
|
Sign up to set email alerts
|

Institutional bricolage in times of crisis

Abstract: How may we understand the occurrence of gradual but significant change following economic crisis? Theories of gradual institutional transformation offer important insights to analyses of long-term institutional change, but have so far shied away from dealing with institutional change during and following crisis, leaving the issue to more traditional critical juncture models. Instead of seeing gradual institutional change originating only in the efforts of rule takers to circumvent existing institutions – poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 35 publications
(42 reference statements)
0
26
0
1
Order By: Relevance
“…Peter Hall's (1993) formative work on policy paradigms, for example, suggested that crisis may pave the way for dominant policy paradigms to be usurped by fresh ideas. More recently, ideational scholars have studied cases where paradigm shifts have not followed crises (Carstensen 2017). This has prompted investigation of subtle modes of ideational change, such as interparadigm shifts (Carstensen and Matthijs 2018), ideational path dependence (Baekkeskov 2016), and relationships between ideas and forms of power (Parsons 2015).…”
Section: Complex Problems Crises and Ideasmentioning
confidence: 99%
“…Peter Hall's (1993) formative work on policy paradigms, for example, suggested that crisis may pave the way for dominant policy paradigms to be usurped by fresh ideas. More recently, ideational scholars have studied cases where paradigm shifts have not followed crises (Carstensen 2017). This has prompted investigation of subtle modes of ideational change, such as interparadigm shifts (Carstensen and Matthijs 2018), ideational path dependence (Baekkeskov 2016), and relationships between ideas and forms of power (Parsons 2015).…”
Section: Complex Problems Crises and Ideasmentioning
confidence: 99%
“…Some aspects of these processes are reproduced in routine practices, whereas other aspects are subject to negotiation, contestation, and justification. Cleaver's concept of institutional bricolage was developed in studies of local institutions for natural resource management in Africa, but is increasingly used in discussing how institutions and policies change in more general terms (see, for instance [28][29][30]). We find the concept highly relevant for exploring the evolution of COP policies in transitional countries in particular.…”
Section: Understanding Policy Formationmentioning
confidence: 99%
“…It has been debated whether the above described concepts constitute descriptive types of change (and continuity), or whether they can be considered as causal mechanisms through which change occurs or not. In the literature, several authors have referred to these concepts using the term "mechanism" (e.g., Beach & Pedersen, 2013;Béland & Powell, 2016;Campbell, 2004;Carstensen, 2017;Falleti & Lynch, 2009;Pierson, 2004). In this respect, causal mechanisms have been conceived in a variety of ways and definitions abound (see e.g., Hedström & Ylikoski, 2010;Mahoney, 2001).…”
Section: Fiscalmentioning
confidence: 99%